NOMA-based Uplink OFDMA Collision Reduction in 802.11ax Networks - Lee, Won Jae; Shin, Wonjae; Ruiz-De-Azua, Joan A.; Capon, Lara Fernandez; Park, Hyuk; Kim, Jae Hyun (International Conference on ICT Convergence, 2021)
Orthogonal frequency division multiple access (OFDMA) is a new feature of medium access control (MAC) protocol adopted in 802.11ax, also called High-Efficiency Wireless (HEW). The OFDMA MAC protocol allows an access point (AP) to divide the wireless channels into smaller chunks called resource units (RUs) and allocate them to different users. There are two types of RUs for the uplink (UL) OFDMA: random access (RA) RU and scheduled access (SA) RU. Only scheduled stations are allowed to access SA RU to avoid collisions; however, a collision occurs if more than one station tries to access the same RA RU. To tackle this issue, we propose a novel UL OFDMA collision reduction method with non-orthogonal multiple access (NOMA). With the help of successive interference cancellation at the receiver side, multiple stations are allowed to share the same RUs at the same time, thereby exploiting the collisions for a better resource utilization efficiency. Simulation results show that the proposed NOMA-based uplink OFDMA method outperforms the conventional orthogonal multiple access-based approach in terms of throughput as well as collision probability.
Keywords: Collision reductions; IEEE 802.11ax; Medium access control protocols; Multiple access; Multiple access collisions; Non-orthogonal; Non-orthogonal multiple access; Random access; Resource units; Uplink orthogonal frequency division multiple access; collision reduction; IEEE 802.11ax; NOMA; Uplink OFDMA; WLAN